Structural Design and Performance Analysis of a Three-dimensional Braided Two-stage Reducer Box - Zhang Weiliang; Wang Xupeng; Ji Xiaomin; Tang Xinyao; Liu Fengfeng; Liu Mingjun (Jixie chuandong)
On the basis of analyzing the movement law of the three-dimensional and five-direction braided yarn, the composite box was designed to be composed of two parts of the braided base and the box wall. On this basis, the braiding and forming principle of the three-dimensional and five-direction braided box was obtained. According to the braiding principle and the yarn movement law, the three-dimensional solid model of the braided box was established, and the finite element analysis of the three-dimensional and five-direction braided box was carried out. The stress of matrix and fiber in the braided composite box was studied by stress and strain analysis results. Under the assumption of ignoring the influence of friction, bearing and other factors on the system, the motion equations of the two-stage gear transmission system with a box body were established, and the numerical analysis of the two-stage gear transmission system was carried out by the Runge-Kutta method to study the influence of excitation on the dynamic characteristics of the assembling and weaving system.